Reconstruction of sediment provenance and transport processes from the surface textures of quartz grains from Late Pleistocene sandurs and an ice-marginal valley in NW Poland - Woronko, Barbara; Pisarska-Jamroży, Małgorzata; Loon, A.J. (Tom) van (Geologos, 2015)
During the Pomeranian phase of the Weichselian glaciation ( 17-16 ka), the Toruń-Eberswalde ice-marginal valley (NW Poland and easternmost Germany) drained water from the Pomeranian ice sheet, while intensive aeolian processes took place across Europe in the foreland of the Scandinavian ice sheet (‘European Sand Belt’). The micromorphology of the quartz grains in the Toruń-Eberswalde ice-marginal valley shows no traces of these aeolian processes, or only vague signs of aeolian abrasion. This is unique among the aeolian sediments in other Pleistocene ice-marginal valleys in this part of Europe. The study of the surfaces of the quartz grains shows that the supply of grains by streams from the south was minimal, which must be ascribed to the climate deterioration during the Last Glacial Maximum, which resulted in a decrease of the discharge of these extraglacial rivers to the ice-marginal valley.